Early Circulating Edema Factor in Inhalational Anthrax Infection: Does It Matter? - Emilie Tessier; Laurence Cheutin; Annabelle Garnier; Clarisse Vigne; Jean-Nicolas Tournier; Clémence Rougeaux (Microorganisms, 2024)
Anthrax toxins are critical virulence factors of Bacillus anthracis and Bacillus cereus strains that cause anthrax-like disease, composed of a common binding factor, the protective antigen (PA), and two enzymatic proteins, lethal factor (LF) and edema factor (EF). While PA is required for endocytosis and activity of EF and LF, several studies showed that these enzymatic factors disseminate within the body in the absence of PA after intranasal infection. In an effort to understand the impact of EF in the absence of PA, we used a fluorescent EF chimera to facilitate the study of endocytosis in different cell lines. Unexpectedly, EF was found inside cells in the absence of PA and showed a pole-dependent endocytosis. However, looking at enzymatic activity, PA was still required for EF to induce an increase in intracellular cAMP levels. Interestingly, the sequential delivery of EF and then PA rescued the rise in cAMP levels, indicating that PA and EF may functionally associate during intracellular trafficking, as well as it did at the cell surface. Our data shed new light on EF trafficking and the potential location of PA and EF association for optimal cytosolic delivery.